Trophic gauntlet effects on fisheries recovery: a case study in Sansha Bay, China. Issue 1 (1st January 2021) - Xie, Bin; Huang, Cheng; Wang, Ya; Zhou, Xijie; Peng, Guogan; Tao, Yancheng; Huang, Jiaju; Lin, Xiaoqing; Huang, Lingfeng
ABSTRACT: Low biological productivity causes ecosystem energy deficiency. Sansha Bay is an important spawning and nursery ground for migratory fish in the East China Sea (ECS). There is significant mariculture in this area, but stock enhancement programs and seasonal fishery closures have failed to recover populations of the commercially important species, Larimichthys crocea . We want to figure out the potential reason of unsuccessful L. crocea resource in recent 30 years. In this study, the trophic status of L. crocea, the food source proportions of L. crocea and zooplankton, and the food web structure and functioning of Sansha Bay was analyzed. A high nutrient low chlorophyll phenomenon was observed: this prevented harmful algal blooms, and phytoplankton growth was restrained by intensive macroalgal culture, resulting in a low abundance of zooplankton in Sansha Bay. Phytoplankton was the most important food source of zooplankton, and zooplankton was the greatest food source of juvenile L. crocea . Analyzed L. crocea suffered from starvation. Crucially, most of the phytoplankton was not used efficiently in the Sansha Bay ecosystem. This study suggests that trophic bottleneck, caused by food limitation, is a potential reason for unsuccessful fishery recovery in enclosed bay with macroalgal culture.